Linzagolix – new perspectives in the pharmacotherapeutic management of uterine fibroids and endometriosis - Paszkowski, Tomasz (Menopause Review/Przegląd Menopauzalny, 2025)
Uterine fibroids and endometriosis are among the most common conditions encountered in gynaecological practice. Fibroids affect 30–70% of women, with up to half experiencing symptoms that significantly impair quality of life (QoL), including anaemia, pain, and pressure-related symptoms. Additionally, fibroids are the sole cause of infertility in 1–3% of women. Endometriosis is the most common gynaecological cause of chronic pelvic pain syndrome and one of the leading causes of infertility. This condition affects between 2% and 10% of women, leading to symptoms that often have a detrimental impact on QoL. For decades, efforts have been underway to develop pharmacological treatments for oestrogen-dependent conditions that would offer both high efficacy and good tolerability. A significant advancement in the treatment of oestrogen-dependent diseases was the introduction into clinical practice of gonadotropin-releasing hormone (GnRH) antagonists. In recent years, publications have demonstrated the promising therapeutic potential of linzagolix in the management of uterine fibroids and endometriosis. It is an oral, small-molecule, non-peptide GnRH antagonist that induces dose-dependent suppression of ovarian function. The aim of this literature review was to evaluate current evidence on the potential applications of linzagolix for the treatment of uterine fibroids and endometriosis. Linzagolix, with or without add-back therapy, significantly alleviates the symptoms of both uterine fibroids and endometriosis in a dose-dependent manner – the therapeutic effect is rapid and sustained. This drug constitutes a valuable addition to existing methods for treating oestrogen-dependent diseases because it enables treatment personalisation allowing for dose adjustment and the optional use of add-back therapy.